The mediating role of employee engagement in the relationship between recruitment & selection and employee retention at the National Bank of Bahrain - Mohammed Alzoraiki; Mahmoud Merza; Ali Ateeq; Marwan Milhem (Banks and Bank Systems)
Employee retention is a critical challenge in the banking sector, with high turnover rates leading to significant costs and operational disruptions. This study investigates the mediating role of employee engagement in the relationship between recruitment and selection practices and employee retention at the National Bank of Bahrain (NBB). A quantitative cross-sectional survey approach was employed, with data collected from a random sample of 257 NBB employees across various departments and hierarchical levels. The study utilized structural equation modeling via SmartPLS to analyze the data. Results indicate that recruitment and selection practices significantly influence employee engagement (β = 0.861, p < 0.000) and employee retention (β = 0.455, p < 0.006). Moreover, employee engagement was found to have a significant positive effect on employee retention (β = 0.406, p < 0.018). Notably, the study reveals a significant indirect effect of recruitment and selection on employee retention through employee engagement (β = 0.35, p < 0.019), confirming the mediating role of employee engagement. These findings emphasize the importance of strategic recruitment and selection practices in fostering employee engagement and enhancing retention rates. The study significantly contributes to the literature on human resource management in the banking sector, providing a deeper understanding of employee engagement’s role in retention and offering practical implications for organizations seeking to improve their talent management strategies and reduce turnover.